The Impact of Simplifications on the Performance of a Finite Element Model of a Macaca fascicularis Cranium. Issue 1 (January 2015) - Fitton, Laura C.; PrôA, Miguel; Rowland, Charlie; Toro‐ibacache, Viviana; O'higgins, Paul; Terhune, Claire; Cooke, Siobhán B.; Laitman, Jeffrey T.
ABSTRACT In recent years finite element analysis (FEA) has emerged as a useful tool for the analysis of skeletal form‐function relationships. While this approach has obvious appeal for the study of fossil specimens, such material is often fragmentary with disrupted internal architecture and can contain matrix that leads to errors in accurate segmentation. Here we examine the effects of varying the detail of segmentation and material properties of teeth on the performance of a finite element model of a Macaca fascicularis cranium within a comparative functional framework. Cranial deformations were compared using strain maps to assess differences in strain contours and Procrustes size and shape analyses, from geometric morphometrics, were employed to compare large scale deformations. We show that a macaque model subjected to biting can be made solid, and teeth altered in material properties, with minimal impact on large scale modes of deformation. The models clustered tightly by bite point rather than by modeling simplification approach, and fell out as being distinct from another species. However localized fluctuations in predicted strain magnitudes were recorded with different modeling approaches, particularly over the alveolar region. This study indicates that, while any model simplification should be undertaken with care and attention to its effects, future applications of FEA to fossils with unknown internal architecture may produce reliable results with regard to general modes of deformation, even when detail of internal bone architecture cannot be reliably modeled. Anat Rec, 298:107–121, 2015. © 2014 Wiley Periodicals, Inc.